Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s13197-011-0324-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of processing conditions for cyanide content reduction in fresh bamboo shoot during NaCl treatment by response surface methodology

Abstract: Abstracts NaCl treatment was optimized for maximum reduction of cyanide content in raw bamboo (Dendrocalamus strictus) shoot using response surface methodology with 4 independent variables like concentration of NaCl, thickness of bamboo shoot, amount of NaCl solution and duration of treatment at 3 levels of each variable. BoxBehnken design was used to select the levels of variables in experimental runs. Cyanide content ranged between 12.8 and 29.6 mg/kg in bamboo shoot after NaCl treatment. The effect of conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Rana et al (2010) also reported the reduction in cyanide content in fresh bamboo shoots during NaCl treatment by response surface methodology. Jaiwunglok et al (2010) reported that high heating Data are presented as mean ± SD (n=3).…”
Section: Resultsmentioning
confidence: 99%
“…Rana et al (2010) also reported the reduction in cyanide content in fresh bamboo shoots during NaCl treatment by response surface methodology. Jaiwunglok et al (2010) reported that high heating Data are presented as mean ± SD (n=3).…”
Section: Resultsmentioning
confidence: 99%
“…Adequacy of the model was determined using coefficient of determination ( R 2 ), F ‐value, and lack‐of‐fit. Effect of variables was deduced from the magnitude and sign of the regression coefficients (Rana and others 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Due to such high profile of nutrition, bamboo shoot is considered as an ideal healthy vegetable. But, bamboo shoots also contain lethal concentration of the anti-nutrient (cyanogen) that can be minimized by boiling it with NaCl solution (Pandey and Ojha 2011;Rana et al 2012). In the Northeastern states of India, bamboo shoots are largely sold in the unprocessed form.…”
Section: Introductionmentioning
confidence: 99%